(untitled) - Jordaan, Marisa

The effect of milk replacer intake and level of crude protein in starter feed on dairy bull calf pre-weaning growth parameters and the carry-over effect on post-weaning growth and profitability (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.